Pengaruh Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan Bidang Sekretariat Dinas Sumber Daya Air dan Bina Marga Kota Surabaya - Rahmadani Wahalima Rosani; Achmad Daengs GS (Jurnal Pengabdian Masyarakat, 2025)
This consider points to decide the impact of work inspiration and work fulfillment on worker execution within the Division of Water Assets and Interstates of Surabaya City. Work inspiration could be a drive within an individual that energizes them to do work. Work fulfillment could be a positive and negative passionate state that emerges from the comes about of investigate on representative work and work involvement. Whereas execution is the result of representative work. The investigate test was 45 respondents. Information collection utilizing surveys, and information analysis techniques utilizing numerous direct relapse helped by SPSS. The comes about of the study demonstrate that work inspiration contains a positive and critical impact on representative execution mostly, work fulfillment contains a positive and noteworthy impact on representative execution mostly, work inspiration and work fulfillment have a positive and critical impact on worker execution at the same time.